Adalékok az 1939-es szovjet-német megnemtámadási szerződés megszületésének körülményeihez I. - Kolontári, Attila (Acta Scientiarum Socialium, 2014)
On the Circumstances of the Birth of the Soviet-German Non-Aggression Pact. Part One The present article examines the main aspects and preliminaries that had led to the signature of this debatable Pact. The present, first part of the article examines the Soviet steps and the criteria based on which they made their decision between the possible alternatives – from the aspects of collective security and isolationism, a class-based approach to international processes and the perception of the capitalist environment. The article provides a detailed examination of British–French–Soviet political and military negotiations, it analyzes the parties’ negotiating strategies and the causes of the failure. The second part of the article, containing a detailed description of the German-Soviet relations of 1939 and of the circumstances of concluding the Pact, is to be published in the next thematic issue of the Acta.